Cantwell, Theresa Squires. Black and white photograph of two men, and one woman with two girls, a boy, and a baby from Theresa Squires Cantwell's personal photograph collection. - Barrett, Terra
Left to right: Theresa Squires, Madeline Squires holding Gertrude Squires, Eileen Squires, William Squires Jr, Patrick Squires, and William Squires Sr.